2021
DOI: 10.1192/bjp.2021.101
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of point-of-care thumb-size bispectral electroencephalography device to quantify delirium severity and predict mortality

Abstract: Background We have developed the bispectral electroencephalography (BSEEG) method for detection of delirium and prediction of poor outcomes. Aims To improve the BSEEG method by introducing a new EEG device. Method In a prospective cohort study, EEG data were obtained and BSEEG scores were calculated. BSEEG scores were filtered on the basis of standard deviation (s.d.) values to exclude signals with high noise. Both non-filtered and s.d.-filtered BSEEG scores were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…All-cause mortality among the study participants were gathered from a review of medical records and obituary records as previously reported ( 26, 27, 29, 30, 34 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All-cause mortality among the study participants were gathered from a review of medical records and obituary records as previously reported ( 26, 27, 29, 30, 34 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our previously published work describes the details of study subjects and recruitment procedures (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Briefly, we identified eligible subjects 18 years old or older from patients at UIHC either admitted as inpatients or visiting the emergency room.…”
Section: Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical variables were gathered through electronic medical chart review, patient interviews, and collateral information from family members [42][43][44][45] . Metformin use, insulin use, and type 2 diabetes mellitus (DM) history were obtained by using the search terms "metformin", "insulin", and "DM" or "diabetes", respectively 12 .…”
Section: Clinical Informationmentioning
confidence: 99%
“…We have previously recruited patients at the University of Iowa Hospital and Clinics (UIHC) for a separate study related to delirium from January 2016 to March 2020 [42][43][44][45] . Among them, we used data from a subgroup of patients recruited from November 2017 to March 2020 who had blood samples collected and processed for the epigenetics analysis [46][47][48] .…”
Section: Study Participants and Recruitmentmentioning
confidence: 99%